Pemanfaatan Tepung Jali, Tepung Mocaf, dan Tepung Kedelai sebagai Bahan Baku Pembuatan Pasta Fettucini dengan Penambahan Ekstrak Bayam Hijau - Anastasia Elvira Rinantina; Alip Suroto; I Gusti Ayu Agung (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Indonesia, as an archipelagic nation, faces considerable challenges in meeting its food requirements in accordance with Law No. 18 of 2012 on Food Security. The country’s heavy reliance on wheat imports, ranking as the largest wheat importer globally, highlights the urgency of diversifying local food sources. This study aims to explore the utilization of jali flour (Coix lacryma-jobi L.), mocaf flour (Modified Cassava Flour), and soybean flour as raw materials for producing fettucini pasta, with the addition of green spinach extract for natural coloring and nutritional enhancement. A quantitative experimental method was employed, testing three formulations of jali and mocaf flour combined with soybean flour. Sensory evaluations were conducted with 35 panelists—comprising trained, semi-trained, and untrained participants—to assess color, aroma, taste, texture, and overall acceptability. The findings revealed that flour composition significantly influenced pasta’s sensory attributes. The F2 formulation (50% jali flour, 50% mocaf flour, 20% soybean flour) achieved the highest acceptance, with average scores across all parameters rated as “liked” to “highly liked.” The incorporation of spinach extract not only imparted an appealing natural green hue but also enhanced the product’s nutritional profile, particularly in iron and dietary fiber content. These results underscore the potential of combining jali and mocaf flours as a nutritious, gluten-free pasta alternative that supports local food diversification and reduces reliance on imported wheat.